Evaluating mathematics–islam integration in higher education: a kirkpatrick model study - Malahayati; Musthofa, Muhammad Wakhid (Pusat Studi Pengembangan Pembelajaran Matematika, 2026)
This study evaluates the effectiveness of implementing the integration–interconnection concept between mathematics and Islamic values in higher education using the Kirkpatrick evaluation model. This study focuses on graduates of the Mathematics Study Program at an Islamic university in Indonesia to assess the impact of post-graduation learning at four levels: reaction, learning, behavior, and results. A quantitative approach was used, with a survey instrument administered to 75 alumni from the 2019 and 2020 batches. The data obtained were analyzed using descriptive statistical methods to measure perceptions of curriculum relevance, competency development, workplace applicability, and value internalization. The findings indicate that the integration of mathematics and Islamic values was positively perceived at the reaction and learning levels, particularly in enhancing conceptual understanding and ethical awareness. At the behavior level, alumni reported moderate application of integrative competencies in professional contexts. In contrast, the results level contributed to character building and professional integrity, though with varying degrees of impact. These outcomes suggest that the integrative learning approach has been partially practical but requires further curricular strengthening to enhance long-term behavioral and professional outcomes. This study contributes empirical evidence on evaluating integrative religious–scientific education using a systematic evaluation framework. It offers insights for improving curriculum Design in mathematics education within Islamic higher education institutions.